On becoming a better supervisor: A deconstruction of autoethnography as method for professional development - O’Neil, S.M. (South African Journal of Higher Education, 2018)
Although not often applied, the autoethnographic method lends itself for use in professional development practices. The literature contains a few examples in which autoethnography is used for this purpose, but with the focus solely on the relationship between mentee and mentor that creates the space for professional development to occur. In the current study, I explored, through a reflective account, the possibilities for using analytic autoethnography for professional development by drawing on the theory of transformative learning. Although there are some drawbacks in using autoethnography, the method may be a valuable addition to current professional development tools if used by the individual practitioner.